THE ODOROUS ATTRACTANT OF THE AMERICAN COCKROACH, PERIPLANETA AMERICANA (L.) : I. QUANTITATIVE ASPECTS OF THE RESPONSE TO THE ATTRACTANT - Wharton, D. R. A. (The Rockefeller University Press, 1954)
1. Procedures have been developed for studying quantitatively the response of the male American cockroach to the odorous attractant of the female. 2. The percentage of male roaches responding to extracts of the attractant of the female has been found to vary with the log of the concentration of the attractant throughout a wide range. 3. Adaptation to the olfactory stimulus has been demonstrated. 4. A theory of adaptation is offered.